Dynamic topography and eustasy controlled the paleogeographic evolution of northern Africa since the mid‐Cretaceous. Issue 5 (19th May 2017) - Barnett‐Moore, N.; Hassan, R.; Müller, R. D.; Williams, S. E.; Flament, N.
Abstract: Northern Africa underwent widespread inundation during the Late Cretaceous. Changes in eustasy do not explain the absence of this inundation across the remainder of Africa, and the timing and location of documented tectonic deformation do not explain the large‐scale paleogeographic evolution. We investigate the combined effects of vertical surface displacements predicted by a series of mantle flow models and eustasy on northern African paleoenvironmental change. We compare changes in base level computed as the difference between eustasy and long‐wavelength dynamic topography arising from sources of buoyancy deeper than 350 km to the evolution of paleoshorelines derived from two interpolated global data sets since the mid‐Cretaceous. We also compare the predicted mantle temperature field of these mantle flow models at present‐day to several seismic tomography models. This approach reveals that dynamic subsidence, related to Africa's northward motion away from the buoyant regions overlying the African large low shear velocity province, amplified sea level rise, resulting in maximum inundation of northern Africa during the Cenomanian and Turonian. By the Cenozoic, decreased magnitudes of dynamic subsidence, reflecting the reduced drawdown effects of slab material beneath northern Africa associated with the impact of the Africa‐Eurasia collision, combined with a comparatively pronounced progressive sea level fall resulted in ongoing region‐wide regression along coastal regions. The temporal match between our preferred model and the paleoshoreline data sets suggests that the paleogeographic evolution of this region since the Late Cretaceous has mainly been influenced by the interplay between eustasy and long‐wavelength dynamic topography arising from large‐scale, subduction‐driven, lower mantle convection. Key Points: We combine the vertical motions of a mantle flow model with eustasy to investigate northern Africa's Cretaceous paleoenvironmental change During the Cenomanian and Turonian, dynamic subsidence amplified sea level rise, resulting in maximum inundation of northern Africa From the latest Cretaceous a decrease in dynamic subsidence combined with a progressive sea level fall resulted in region‐wide regression